PERAN DAN FUNGSI MUSIK DOL DALAM UPACARA TABOT DI KOTA BENGKULU - Sumarta, Abi; Tarwiyah, Tuti; Saryanto, Saryanto (Jurnal Penelitian Musik, 2022)
Dol music is a musical ensemble consisting of big dol, small dol and tassa. This music is the traditional music of Bengkulu. This music has its own role and function in accompanying the Tabot Ceremony in Bengkulu. The purpose of this research is to describe the role and function of Dol music in the Tabot ceremony in the city of Bengkulu.This study uses a descriptive qualitative research method. Data collection techniques were carried out by observation, interviews and documentation. Data analysis was carried out with the stages of data reduction, data display, and drawing conclusions. The results of the study showed that Dol's music played the role of accompaniment to the Tabot ceremony series from the opening to the closing series. In carrying out this role, Dol's music functions as a validator for social institutions and as a form of symbol. The rhythm of Dol music at the Tabot ceremony is a symbol of the atmosphere during the war, namely the rhythm of Sweri as a symbol of triggering enthusiasm, Tamatam as a symbol of solace or releasing fatigue, and Swena/Meradai as a symbol of mourning.